Integrating STEM Education through Project-Based Learning: Towards Excellence in Nursing Students - Varee, Acha; Somsap, Yaowares (Journal of The Royal Thai Army Nurses, 2023)
The leading trail of the country to meet the excellent in the healthcare service and international standard is the outstanding and value-added service. This is the challenge for creating the nursing curriculum to meet the implementation with perfect skills. The nursing curriculum is the basis to enhance the 21st Century skills of the nurses, for solving the problems in the implementation, create more experience, skills and new innovation. The project-based learning by integrating the STEM Education by active learning is corresponding to the knowledge management for the future of the production section and healthcare. The purposes of this article are introduce the project-based learning by integrating the STEM Education for the nursing students which focus on the definition, the nursing curriculum, the Interdisciplinary integration, the evaluation, the role of nursing instructors and the case study. The know-how and the skills of the nursing students can solve the problems in practice, more study and self-development to the disruption change for the nursing students and can utilize the informations to develop the nursing curriculum towards excellence in nursing students.